The Effect of Debt Policy, Investment Decision , and Profitability on Firm Value (at Food and Beverages Companies Listed on the Indonesian Stock Exchange in 2017 – 2019 - Iin Indarti; Wenny Ana Adnanti; Nofitria Puspita Cahya Sari (LPPM STIE Anindyaguna, 2021)
The purpose of this study was to analyze the effect of debt policy (DAR), investment decision (PER) and profitability (ROE) on firm value at Food and Beverages companies listed on the Indonesian Stock Exchange in 2017 – 2019 either partially or simultaneously. The population used was financial report of Food and Beverages companies totaling 82 data or research populations. The samples were 66 data. The technique sampling used non probability technique, specified in judgement sampling. This study used multiple linear regression. The result showed that debt policy (DAR) had no effect on firm value, investment decision (PER) had a negative and significant effect on firm value, and profitability (ROE) had a positive and significant effect on firm value. Simultaneously it showed that debt policy (DAR), investment decision (PER) and profitability (ROE) significantly influenced firm value